Dreamwork, art worlds and miracles in Malaysia - Farrer, Douglas S. (World Art, 2020)
Dreamwork recorded in the Malay art world questions the occult power of artistic agency. As I did participant observation in Malaysia and Singapore, the artist Mohammad Din Mohammad divulged knowledge of Sufi lore, shamanic healing, and Malay martial arts (silat). On a quest to comprehend, discover, create and articulate esoteric skills, secret knowledge and mysterious artifacts, the artist produced fine art paintings, talismanic jewelry and assemblage sculptures. These were to be used in psychic defence, dream incubation, for inspiration, and as medicine. A field site discussion as to whether a reported vision of a mysterious shadow warrior is a true, false, or meaningless dream forms the kernel of a dreamwork dialogue regarding miraculous agency. The artwork raises questions pertaining to sorcery, Islam, agency, and power in Southeast Asia, revealing a political battle of Sufi versus Wahhabi notions in the constitution of Malay modernity.
Created from Fastlane, Scopus look-up
Keywords: agency; art worlds; dreamwork; healing; miracles; power